Impacto da torrefação nas características fisico-químicas do bagaço de cana de açúcar: potencial de cogeração de energia e avaliação do ciclo de vida - Santos, Maria Isabel Silva dos [UNESP] (2022)
Agribusiness and its entire production chain generate a substantial amount of organic waste that can cause several environmental impacts if not correctly disposed. In this context, an interesting possibility lies in the energy reuse processes and, therefore, pre-treatment processes that could potentially increase the generation of energy, such as torrefaction. Thus, the present work seeks to analyze how torrefaction affects the composition of sugarcane bagasse (SCB) and the environmental impacts of the addition of this valorization process to a conventional cogeneration powerplant. The torrefaction process was carried out in 4 different scenarios: 230°C for 30 and 45 minutes; and 280°C for 30 and 45 minutes. Ultimate analyses (CHN-O), thermogravimetric analyses and characterization of lignocellulosic composition were conducted for raw and torrefied sugarcane bagasse. The experimental data served as basis for modeling a cradle-to-gate environmental life cycle analysis (LCA) of a theoretical energy cogeneration system that contains a torrefaction unit. Results show that mild torrefaction at 230°C emitted mainly moisture and volatile matter from SCB; whilst severe torrefaction, at 280°C, degraded significantly the structure of the biomass. The values of high heating values increased by about 20% for the lowest temperature torrefaction and by 27% for the more severe scenario. Torrefaction at 230°C reduced the mass of BCA by around 13% - 15.6%, while at 280°C the reduction was around 25 - 25.8%. The more accentuated mass loss in severe torrefaction was responsible to diminishes the energy yield of the biomass. The LCA results show that the main environmental impacts of the cogeneration process fueled by sugarcane bagasse are related to the emission of greenhouse gases. The best performance in terms of both energetic valorization and environmental impacts was obtained by torrefaction at 230°C for 30 minutes.